A vida dos conceitos: reflexão e contradição na Doutrina da essência da Ciência da lógica de Hegel - Renata Inarah Guerra Santos (2016)
With the Science of logic, Hegel intends to present a critical reconstruction of the determinations of thought. In the Modernity distinguished by transcendental philosophy, understanding prevails over philosophy, and reason loses its constitutive role; its use becomesmerely regulative. The diagnosis of the necessity of philosophy emerges from the split between understanding and reason, the very split that defines Modernity. To the understanding is given the capacity of knowing the empirical world, whereas falls to reason the capacity of ordering and concatenation of understanding and its judgements. The speculative principle the identity between subject and object was inherited from the Kantian transcendental deduction. Nevertheless, that identity would be only a subjective synthesis. For Hegel, philosophy, in order to be science, must sublate the split between understanding and reason, and comprehend that the a priori and the a posteriori constitute themselves in a reciprocal movement of reason itself. This step implies recognizingcontradiction as the constitutive element of matter itself. Therefore, it was required to break with representative thinking, asserting in its place objective thinking. That split, reaffirmed at the basis of Kantian philosophy, is however the starting point for the necessity of the Hegelianconcept of objective thinking. The unfolding of objective thinking is found in the Science of logic, and, precisely, in the Doctrine of essence, the place in which Hegel elaborates his immanent critique of the traditional categories of metaphysics, and the laws of understanding. This dissertation aims to present a study on the Hegelian critical reconstruction of determinations of reflection identity, difference, diversity, opposition, and contradiction to point out the specificity of objective thinking, which in our view is revealed in the determination of contradiction as the essential ground for actuality